2014
DOI: 10.1021/jp4081965
|View full text |Cite
|
Sign up to set email alerts
|

Red Photoluminescence from Bi3+and the Influence of the Oxygen-Vacancy Perturbation in ScVO4: A Combined Experimental and Theoretical Study

Abstract: We report on a red-emitting ScVO4:Bi3+ phosphor which does not show excitation at energies below 2.88 eV (430 nm). X-ray diffraction, time-resolved, and quantitative photoluminescence (PL) spectroscopy were employed to characterize relations between crystal structure and luminescence properties of the material. Results show that incorporation of Bi3+ renders the blue photoemission of blank ScVO4 to red. Dynamic luminescence analysis between 10 and 300 K reveals a complicated dependence of energy transfer from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
137
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 173 publications
(145 citation statements)
references
References 55 publications
8
137
0
Order By: Relevance
“…The red phosphor should be excitable by blue light (for instance with a wavelength between 450 nm to 480 nm) and not by green light. 1,[6][7][8][9] In this way the composite system can efficiently avoid the reabsorption of the as-generated white light. This idea has stimulated research on red phosphors activated by rare earths, with outstanding candidates being divalent europium-doped (oxy)nitrides.…”
Section: Introductionmentioning
confidence: 99%
“…The red phosphor should be excitable by blue light (for instance with a wavelength between 450 nm to 480 nm) and not by green light. 1,[6][7][8][9] In this way the composite system can efficiently avoid the reabsorption of the as-generated white light. This idea has stimulated research on red phosphors activated by rare earths, with outstanding candidates being divalent europium-doped (oxy)nitrides.…”
Section: Introductionmentioning
confidence: 99%
“…have reported the greenish‐yellow luminescence of Bi 3+ ions in lanthanide vanadate phosphors. Whereas red luminescence in scandium vanadates and blue emission in calcium antimonates were reported by Kang et al . and Yao et al .…”
Section: Introductionmentioning
confidence: 84%
“…The electronic structure of zircon-type orthovanadates under pressure was investigated and it was reported that cation substitution influence the electronic states [8]. Red shift of the vanadate band gap observed with the cation substitution, further results in decrease of the band gap as observed with the Bi doping in these orthovanadates [9,10]. Errandonea et al [2] studied the transition pressure of ABO 4 orthovanadates, and found it to be in the range of 7e8 GPa independent of cation size, and also observed two transitions i) zircon / scheelite ii) scheelite / monazite but in the case of ScVO 4 only first transition is observed, whereas in the case of EuVO 4 , LuVO 4 , both the transitions are observed.…”
Section: Introductionmentioning
confidence: 99%